Emerging ecosystem-centric business models for sustainable value creation - Ziouvelou, Xenia, 1975-; McGroarty, Frank (Francis Joseph Anthony) (Advances in business strategy and competitive advantage., 2022)
"This book explores emerging technology-enabled ecosystems and ecosystem-centric business models in theory and practice from a business and technological perspective"--